Syndrome Of Inappropriate Antidiuretic Hormone Secretion (SIADH) In Inflammatory Diseases And Its Effect On Heart (Latakia University Journal -Medical Sciences Series, 2024)
Although Hyponatremia is a well-known complication of many inflammatory diseases, However, the pathophysiology in this context remained poorly understood until recently. There is now considerable evidence indicating the important role played by inflammatory cytokines, especially IL-6, in the non-osmolar secretion of Vasopressin, which is the primary cause of syndromic formation during systemic inflammatory diseases. The seriousness of serum sodium deficiency occurring in the context of SIADH is not limited to its neurological symptoms, but also to its effects on cardiac action potential and conductive pathways in the heart